Mistralazhdarcho maggii, gen. et sp. nov., a new azhdarchid pterosaur from the Upper Cretaceous of southeastern France. Issue 4 (4th July 2018) - Vullo, Romain; Garcia, Géraldine; Godefroit, Pascal; Cincotta, Aude; Valentin, Xavier
Abstract: A series of pterosaur bones from the Upper Cretaceous (Campanian) of Velaux (Bouches-du-Rhône, southeastern France) is described. This material, including both cranial and postcranial elements found in close association and likely belonging to a single immature individual, is assigned to a new genus and species of azhdarchid pterosaur, Mistralazhdarcho maggii . This large-sized taxon (wingspan ca. 4.5 m in the holotype, possibly reaching 5–6 m in mature individuals) is characterized by a slightly downturned mandibular symphysis that shows a 'V'-shaped cross-sectional profile and bears a well-developed, anteriorly located median eminence on its dorsal surface. The presence of a median eminence suggests that Mistralazhdarcho might be closely related to Alanqa from the Cenomanian of Morocco. The material described here represents the first partial skeleton of a pterosaur recovered from the Late Cretaceous deposits of western Europe, and the new taxon is one of the most completely known European azhdarchids. Mistralazhdarcho is intermediate in size between the medium-sized genus Eurazhdarcho and the giant-sized genus Hatzegopteryx, two azhdarchids from the Maastrichtian of Romania. The discovery of Mistralazhdarcho suggests the presence of a third azhdarchid size class in the continental ecosystems of the latest Cretaceous European archipelago. http://www.zoobank.org/urn:lsid:zoobank.org:pub:00DEB0A5-6B18-42A4-A4BF-79EC9EEF0230 Citation for this article: Vullo, R., G. Garcia, P. Godefroit, A. Cincotta, and X. Valentin. 2018. Mistralazhdarcho maggii, gen. et sp. nov., a new azhdarchid pterosaur from the Upper Cretaceous of southeastern France. Journal of Vertebrate Paleontology. DOI:10.1080/02724634.2018.1502670.